Model Perancangan Pembelajaran Blended Mata Kuliah Keilmuan Akuntasi Di ITB-AD Jakarta - Widyat Nurcahyo; Yumniati Agustina; Adi Rizfal Efriadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2019)
This research aims to build a blended learning design model that can be used effectively and systematically by lecturers in developing blended learning systems for accounting subjects at Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta (ITB-AD). It is important because the research results model can be immediately utilized by accounting lecturers to design blended learning. This study is a design based research in the form of formative research. Data collected by qualitative means through interviews, document analysis, surveys, and observations. The contribution of this study is in the form of a model that is built based on existing learning design models, specifically adapted for learning accounting subjects in ITB-AD, according to the characteristics of students, lecturers, and institutions. The model developed is called the BLADe model.